2021
DOI: 10.3389/fnagi.2020.573454
|View full text |Cite
|
Sign up to set email alerts
|

Novel Subgroups in Subarachnoid Hemorrhage and Their Association With Outcomes—A Systematic Review and Meta-Regression

Abstract: Background and Purpose: Subarachnoid hemorrhage (SAH) has long been classified into two main forms, aneurysmal SAH (aSAH) and non-aneurysmal SAH (naSAH), but the related risk factors for aSAH and naSAH are heterogeneous. Our objective was to determine the risk factors for SAH of known or unknown origin with respect to diagnostic evaluation in a large patient cohort. We sought to determine whether our classification system can further predict middle long-term stroke and death.Methods: We performed a systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Using the G*Power software (v3.1.9.6, University of Kiel, Germany) for calculating the a priori sample size power, for repeated measurement analysis, assuming an alpha error probability of 0.05, a power of 0.80, and two independent groups (aSAH and smSAH), with 6 different time points, and no information about correlations among the serial measurements, 26 expecting a small-to-medium effect size (with f ranging from 0.20 to 0.25) based on the existing literature, 10 the overall minimum sample size requested was found to vary between 24 and 36, with the minimum requested number of smSAH patients ranging from 4 to 5, assuming a 15% prevalence rate. Furthermore, post-hoc power analysis of the sample size demonstrated the statistical robustness of our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the G*Power software (v3.1.9.6, University of Kiel, Germany) for calculating the a priori sample size power, for repeated measurement analysis, assuming an alpha error probability of 0.05, a power of 0.80, and two independent groups (aSAH and smSAH), with 6 different time points, and no information about correlations among the serial measurements, 26 expecting a small-to-medium effect size (with f ranging from 0.20 to 0.25) based on the existing literature, 10 the overall minimum sample size requested was found to vary between 24 and 36, with the minimum requested number of smSAH patients ranging from 4 to 5, assuming a 15% prevalence rate. Furthermore, post-hoc power analysis of the sample size demonstrated the statistical robustness of our study.…”
Section: Methodsmentioning
confidence: 99%
“… 5 , 6 Although even in these patients subarachnoid blood is not harmless, and recent studies have shown possible vasospasm, re-bleeding, hydrocephalus, seizure, cognitive impairment, and depression among sequelae, 7–9 the prognosis of smSAH patients is much better when compared with aneurysmal SAH (aSAH). 10 …”
Section: Introductionmentioning
confidence: 99%
“…Patients with PNSAH have a nearly normal life expectancy, and no restrictions should be imposed on these patients. In a systematic review by Wang et al ( 85 ) patients with PNSAH showed a 13-month survival rate of 97.2% and a 30-month survival rate of 98.6%. In Greebe et al's ( 84 ) report of PNSAH consisting of 160 patients, with a total number of 1,213 patient-years, no new SAH occurred, and 11 patients died; however, none of the deaths were direct consequences of PNSAH, and patients have a normal life expectancy.…”
Section: Definition and Variantmentioning
confidence: 99%
“…Clinical variables were selected based on previous recommendations which included general risk factors, baseline demographic data, and vascular risk factor data 1 . This included gender, age, blood pressure, lipid profile, glucose levels, smoking history, surgical time, aneurysm location and size, initial severity of bleed, clinical markers of EBI, SEBES scale 21 , Hunt-Hess scale 22 , modified Fisher grade, and Glasgow Coma Scale (GCS) at time of admission, and MoCA and MMSE at 2-months post-discharge (Details in online supplemental materials, Clinical Variables).…”
Section: Methodsmentioning
confidence: 99%
“…The latest delineation of subgroups within the subarachnoid space provides a theoretical basis for more accurate diagnosis and treatment of subarachnoid hemorrhage (SAH) 1 . Specifically, aneurysmal subarachnoid hemorrhage (a-SAH) is a subtype of hemorrhage stroke associated with high morbidity and mortality, constituting a significant cause of neurological disease 1,2 . Common complications following a-SAH include early brain injury (EBI), symptomatic vasospasm, brain edema, delayed cerebral ischemia (DCI), delayed deficits, and cognitive impairments (CI) 3,4,5 .…”
Section: Introductionmentioning
confidence: 99%